PENGARUH RISK TOLERANCE, OVERCONFIDENCE DAN LITERASI KEUANGAN TERHADAP KEPUTUSAN INVESTASI PADA KOMUNITAS STUDI PASAR MODAL DI UNIVERSITAS METHODIST INDONESIA - Nadeak, Octavia; Mitha Cristhina Ginting; Farida Sagala (Jurnal Bisnis Manajemen dan Akuntansi (BISMAK), 2025)
This study aims to examine the influence of risk tolerance, overconfidence and financial literacy on investment decisions in the capital market study community at Methodist University Indonesia. This type of research is a quantitative research that uses primary data. The data analysis method used multiple linear regression with as many as 200 student respondents who were registered as members of the Capital Market Study Community at Indonesian Methodist University. This study took 50 respondents who met the sample criteria using the purposive sampling method. The data analysis method applied in this study is descriptive statistics. The data collected was then processed using the SPSS analysis tool version 26. The results of the study with the t-test showed that the risk tolerance variable had a negative and significant effect on investment decisions, the overconfidence variable had a positive and significant effect on investment decisions, and the financial literacy variable had a positive and significant effect on investment decisions. The results of the study with the F test show that risk tolerance, overconfidence, and financial literacy have a significant effect simultaneously on investment decisions.